OGBN O07 Factors in recurrence following 862 giant paraesophageal hernia repairs - Nguyen, Chu Luan; Zhou, Michael; Tovmassian, David; Seyfi, Doruk; Isaacs, Anna; Gooley, Suzanna; Falk, Gregory (British journal of surgery, 2023)
Background Repair of giant paraesophageal hernia (PEH) is associated with a considerable hernia recurrence rate by objective measures. This study evaluated trends in outcomes of laparoscopic non-mesh repair of giant PEH over 30 years, and factors associated with anatomical recurrence. Methods Data was extracted from a single-surgeon prospective database of laparoscopic repair of giant PEH from 1991-2021. Upper endoscopy was performed within 12 months postoperatively and selectively thereafter. Any supra-diaphragmatic stomach was defined as anatomical recurrence. Cases were chronologically divided into tertiles with trends in casemix, operative factors and outcomes evaluated. Patient and hernia characteristics, and technical operative factors, including “composite repair” (360-degree fundoplication with esophagopexy and cardiopexy to right crus), were evaluated with univariate and multivariate analysis. Results 862 repairs met selection criteria. Mean age 69.3years, majority(65.8%) female and hernia type III(87.4%) with median hernia size 66%. There was an increasing proportion of “composite repair” after the first decade(Group1, 2.7%;Group2, 81.9%;Group3, 100%;p<0.001).There were less anatomical hernia recurrence(Group1, 36.6%;Group2, 22.9%;Group3, 22.7%;p<0.001) over time. The overall anatomical recurrence rate was 27.3% with median followup 33months(IQR 16, 68). There were 10(1.2%) Clavien-Dindo grade ≥III complications including two perioperative deaths(0.2%). Multivariate analysis identified age<70years, presence of Barrett’s, absence of “composite repair”, and hiatus closure under tension as independent factors associated with recurrence(HR1.27,95%CI0.88-1.82,p=0.01;HR1.58,95%CI1.12-2.23,p=0.009;HR1.72,95%CI1.2-2.44,p=0.002;HR2.05,95%CI1.33-3.17,p=0.001,respectively). Conclusions Hernia recurrence rates decreased with increasing case volume. This coincided with the increasing adoption of “composite repair”, supporting the possible improvement in recurrence rates with this approach. Repair was associated with substantial anatomical recurrence associated with patient and technique factors. Patient factors included age <70 years, Barrett’s esophagus, and hiatus tension. “Composite repair” was associated with lower recurrence rate.